Surgical Care Practitioners: Regulation and Revalidation: A Discussion. Issue 10 (October 2014) - Quick, J; Hall, S
The regulation of healthcare professionals is far from new. It continues to evolve, responsive to changes in the professional workforce and the needs of society.